Executive Committee Minutes 2019-09-19 - Academic Senate:::::::::
Agenda approved. Minutes of 9/5/19 approved. Chair Report. President Report. Provost Report. From FSAC: Revision to the Emeritus Policy – Approved as business for the Senate. From EPC: Minimal Revision to the EMBA program – Approved for the Senate consent calendar. From EPC: GERN Discontinuances – Approved as business for the Senate. Report on Graduate Education at SSU – Approved for Senate agenda. Vice Chair Report. VP of A&R Report. VP for Student Affairs Report. Associated Students Report. APARC Report. EPC Report. FSAC Report. CFA Report. Senate agenda approved. Good of the Order.